2014
DOI: 10.1080/15222055.2014.951812
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐Glucans and Mannan Oligosaccharides Enhance Growth and Immunity in Nile Tilapia

Abstract: We studied the effects of a combination of dietary beta‐glucans (β‐G) and mannan oligosaccharides (MOS) on Nile Tilapia Oreochromis niloticus. Three‐hundred‐sixty fingerlings (mean mass ± SD = 8.7 ± 0.4 g) were separated into three groups (G1, G2, and G3) of 120 fish; G1 (control group) was fed a basal diet, whereas G2 and G3 were fed prebiotic‐supplemented diets at final levels of 1.5 and 3.0 g/kg feed, respectively. Each group was subdivided into two subgroups: subgroup A was fed for 60 d to evaluate growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 75 publications
4
40
1
Order By: Relevance
“…Additional factors, including colonization in the gut, attachment site, viability, stress factors and experimental and environmental conditions, might affect probiotic mechanisms [101e103]. In our previous study, the use of a combination of dietary beta-glucans (b-G) and mannan oligosaccharides (MOS) resulted in better performance in terms of growth rate, intestinal morphology, immune response and disease resistance, than the use of B. amyloliquefaciens tilapia under the same circumstances [23,104]. Similarly, Ngamkala et al [105] reported that glucan elicited better immunostimulation and resistance against A. hydrophila in tilapia than the probiotic L. rhamnosus.…”
Section: Discussionmentioning
confidence: 98%
“…Additional factors, including colonization in the gut, attachment site, viability, stress factors and experimental and environmental conditions, might affect probiotic mechanisms [101e103]. In our previous study, the use of a combination of dietary beta-glucans (b-G) and mannan oligosaccharides (MOS) resulted in better performance in terms of growth rate, intestinal morphology, immune response and disease resistance, than the use of B. amyloliquefaciens tilapia under the same circumstances [23,104]. Similarly, Ngamkala et al [105] reported that glucan elicited better immunostimulation and resistance against A. hydrophila in tilapia than the probiotic L. rhamnosus.…”
Section: Discussionmentioning
confidence: 98%
“…Supplemented diets with 0.1% β‐glucan improved Nile tilapia weight gain (Welker, Lim, Yildirim‐Aksoy, & Klesius, ). Diets containing β‐glucan and mannan oligosaccharides (MOS) have also previously been found to improve the growth performance of Nile tilapia and beluga, Huso huso (Selim & Reda, ; Ta'ati, Soltani, Bahmani, & Zamini, ). In our experiment, feed intake increased significantly with increasing levels of S. cerevisiae extract in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this study, it is particularly interesting that calreticulin is directly involved in the synthesis of mucins [53], the main macromolecule of mucus. Yeast-derived prebiotic dietary supplements have been linked to an increase in mucus layer thickness [54] and goblet cell number [5,25] in the gut. Furthermore, mucin 5B was up-regulated by three-fold in the skin mRNA of common carp Cyprinus carpio fed a β-glucan, a type of YCW extract [55].…”
Section: Discussionmentioning
confidence: 99%